The Right to Cyborgization in Slovenia - Ivanc, Blaž (Medicine, Law & Society, 2019)
The article deals with the legal aspects of the phenomenon of cyborgization. There is a structured debate about legal and ethical admissibility of the use of scientific and technological interventions in the field of biomedicine, by which we transform or supplement the functioning of the natural human organism in the direction of an increasingly artificial human being. In the discussion, we ask ourselves, to what extent or in what sense it’s possible to talk about the right of a person to cyborgization. After discussing the typology of scientific and technological interventions or technologies that can be classified in the field of cyborgization, the discussion draws attention to ethical dilemmas. First, it identifies the distinction between medically indicated interventions, which means cyborgization, and medically unindicated. In the next step, the discussion deals with the distinction between cyborgization interventions, which must be controlled from the point of view of ethics, and other interventions. It tries to define the typology of existing or future unethical and unlawful interventions. Finally, the discussion opens the questions on the way, content and approach to the legal regulation of the phenomenon of cyborgization and attempts to assess the quality of the current legal regulation of that area.